Protective Effects of Fluticasone on Allergen-Induced Airway Responses and Sputum Inflammatory Markers. Issue 4 (3rd August 2000) - Parameswaran, Krishnan; Inman, Mark D; Watson, Rick M; Morris, Marilyn M; Efthimiadis, Ann; Ventresca, Pietro G; Lam, Raymond; O'Byrne, Paul M; Hargreave, Frederick E
Abstract : BACKGROUND: A direct comparison of the protective effects of single and regular doses of inhaled glucocorticoid on allergen-induced asthmatic responses and inflammation has not been made. OBJECTIVE: To compare the effects of pretreatment with fluticasone 250 µg 30 min before allergen inhalation and two weeks of 250 µg twice daily (last dose 24 h before challenge) with single and regular (twice daily) placebo doses on early and late asthmatic responses, induced sputum cell counts and measures of eosinophil activation at 7 h and 24 h, and methacholine airway responsiveness at 24 h. PATIENTS AND METHODS: Ten mild asthmatic patients were studied in a randomized, double-blind, placebo controlled crossover study. RESULTS: Regular fluticasone increased the baseline mean provocative concentration of methacholine to cause a 20% fall (PC20 ) in forced expiratory volume in 1 s (FEV1 ) from 2.6 to 6.4 mg/mL (P<0.05) and lowered the eosinophil count from 3.1% to 0.4% (P<0.05) compared with regular placebo. Neither single nor regular fluticasone had any effect on the early asthmatic response. Single fluticasone attenuated the late asthmatic response, the mean ± SEM maximum percentage fall in FEV1 (10.8±3.6 compared with single placebo 18.8±3.5, P=0.03), the allergen-induced increase of airway responsiveness (P<0.05), and the eosinophilia (P<0.005) and activated eosinophils at 7 h (P<0.01) but not at 24 h. Regular fluticasone also attenuated the late asthmatic response (11.1±2.5) compared with regular placebo (19.6±4.5), but this was not statistically significant and did not protect against the induced increase in airway responsiveness or the sputum eosinophilia. CONCLUSION: Two weeks of regular inhaled fluticasone discontinued 24 h before allergen challenge does not offer any additional protection against the early or late asthmatic responses, increased airway responsiveness or sputum eosinophilia compared with a single dose of 250 µg immediately before allergen challenge, despite increasing baseline PC20 and decreasing sputum eosinophilia prechallenge. The significance of the protective effect of a single dose of inhaled steroid before an allergen inhalation and the duration of the protective effect need further investigation.